DESIGN AND DEVELOPMENT OF WEB-BASED BLOOD DONATION APPLICATION WITH RAPID APPLICATION DEVELOPMENT METHOD(RAD - Daniel Apdianto Herman; Hendry Wijaya (Universitas Internasional Batam, 2022)
One of the health activities that the public is most aware of is blood donation. However, there are still many obstacles in finding donations or those who want to donate blood. Therefore we need a system that can facilitate these obstacles. Research on this blood donation application aims to share information with the public about finding blood donors and wanting to donate its blood easily. One of method that can be used in this case is rapid application development method which has the stages concist of requirements planning, system design, and implementation. The conclude result of this study will be a web-based blood donation application.